Transplant Tolerance, Not Only Clonal Deletion - Hall, Bruce M.; Verma, Nirupama D.; Tran, Giang T.; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2022)
The quest to understand how allogeneic transplanted tissue is not rejected and how tolerance is induced led to fundamental concepts in immunology. First, we review the research that led to the Clonal Deletion theory in the late 1950s that has since dominated the field of immunology and transplantation. At that time many basic mechanisms of immune response were unknown, including the role of lymphocytes and T cells in rejection. These original observations are reassessed by considering T regulatory cells that are produced by thymus of neonates to prevent autoimmunity. Second, we review “operational tolerance” induced in adult rodents and larger animals such as pigs. This can occur spontaneously especially with liver allografts, but also can develop after short courses of a variety of rejection inhibiting therapies. Over time these animals develop alloantigen specific tolerance to the graft but retain the capacity to reject third-party grafts. These animals have a “split tolerance” as peripheral lymphocytes from these animals respond to donor alloantigen in graft versus host assays and in mixed lymphocyte cultures, indicating there is no clonal deletion. Investigation of this phenomenon excludes many mechanisms, including anti-donor antibody blocking rejection as well as anti-idiotypic responses mediated by antibody or T cells. This split tolerance is transferred to a second immune-depleted host by T cells that retain the capacity to effect rejection of third-party grafts by the same host. Third, we review research on alloantigen specific inhibitory T cells that led to the first identification of the CD4+CD25+T regulatory cell. The key role of T cell derived cytokines, other than IL-2, in promoting survival and expansion of antigen specific T regulatory cells that mediate transplant tolerance is reviewed. The precise methods for inducing and diagnosing operational tolerance remain to be defined, but antigen specific T regulatory cells are key mediators.